Evaluation of correction in shaping body mass women first adulthood with different personal features - S.A. Smaylova (Physical Education of Students)
Assessed the effectiveness of training method of the "Shaping Classic" on the catabolic program correction of body weight the first mature age women with different personality characteristics. The study involved 20 women aged 26 - 30 years with a body mass index above average and high. Conducted anthropometric measurements. Used physiological tests, step test Prohorovtseva, engine test, psychodiagnostic methods. The efficiency of the program in reducing total body weight and body fat. The positive impact of the program on the functional state of the cardiovascular system and the musculoskeletal system is shown. Found that particular dispositions eating and self-esteem of women may reduce the level of impact of training. It is revealed that these features contribute to devaluing recommendations coach and weaken the motivation to train.